THE USE OF SYNONYMS IN THE POETRY OF ERKIN VAKHIDOV - Yakubova Feruza Anvarovna (Galaxy International Interdisciplinary Research Journal, 2022)
The article explores the use of synonyms in the poetry of the poet Erkin Vakhidov, the study of synonyms in the poet’s work and their aspects of increasing artistic effectiveness, as well as methodological peculiarities in the language of poetry, more than one ensures image clarity through the sequential use of unfamiliar words, which not only uses ready-made semantic words that are present in the language, but also non-semantic according to the needs of the artistic image. Use them in such a way that these words are perceived in the text as meaningful words.